Edukasi dan Pelatihan Pemanfaatan Pewarna Alami untuk Peningkatan Kualitas Produk Pangan di Kawasan Ekowisata Isyo Hills, Rhepang Muaif, Kabupaten Jayapura - Vita Purnamasari; Lisye I. Zebua; Henderina J. Keiluhu; Evie L. Warikar; Fawuni G.A.G. Rumbrawer; Raini Panjaitan; Jeirel Wattilete; Selina A. Mansawan; Seramina R.T. Sawegu (Bakti Hayati: Jurnal Pengabdian Indonesia, 2026)
The Isyo Hill’s Bird Watching Ecotourism Area in Rhepang Muaif Village, Nimbokrang District, Jayapura Regency is a tourist destination that welcomes visitors from various countries, with food and beverage services provided by local culinary groups. The main challenge in culinary presentation is creating dishes that are not only delicious but also visually appealing. The use of natural colorants is a safe and health-beneficial alternative to synthetic dyes. The local community is already familiar with several natural color sources such as kesumba keling fruit (Bixa orellana), turmeric (Curcuma longa), and teak leaves (Tectona grandis), and has the potential to develop additional natural color sources, such as butterfly pea flowers (Clitoria ternatea). This community service initiative aims to enhance the community’s knowledge and skills in utilizing natural colorants in food and beverages. The implementation method consists of three stages: outreach, discussion through a Focus Group Discussion (FGD), and practical training. The results of the activity demonstrate an increase in participants’ understanding and ability to apply natural colorants, as evidenced by processed products such as steamed sponge cake and sliced nagasari using butterfly pea flower colorant, as well as beverages made from butterfly pea flower extract. Additionally, a guidebook containing information on natural colorants and processed food recipes was compiled as an output of the activity. This initiative is expected to support the enhancement of the quality of healthy, appealing, and value-added local culinary offerings for the ecotourism sector at Isyo Hill’s.